COMPARATIVE ANALYSIS OF PLASTIC WASTE MANAGEMENT STRATEGIES: A Case Study Of Indonesia And Malaysia 2018-2023 - Januari Pratama Nurratri; Cahya Maghfira Prasetya; Jihan Fadhilah Hanun Rasuli (Halu Oleo University, 2024)
The problem of plastic waste is profound in every country in the world. This is because plastic is the most widely produced material and is difficult to degrade in the environment. Indonesia and Malaysia are countries that have serious plastic waste problems. Indonesia and Malaysia are the top five countries producing plastic waste in Southeast Asia (Arumdani, Puspita, & Budiharjo, 2021). This is what the Indonesian and Malaysian governments are concentrating on to resolve environmental pollution due to the ever-increasing volume of plastic waste. This journal uses a comparative study to compare the efforts of Indonesia and Malaysia in dealing with the plastic waste problem. To solve the plastic waste problem, the Indonesian government has established several regulations and programs to meet the SDGs targets. The Malaysian government also implemented regulations and behavioural changes to reduce plastic waste, which aligns with the Basel Convention, which regulates hazardous wastes, including plastic waste. Facing almost similar problems, Indonesia and Malaysia continue to strive to solve the plastic waste problem by following the priorities and targets of their respective countries.